2018
DOI: 10.1038/s41467-018-07755-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring drug nanocarriers in human blood by near-infrared fluorescence correlation spectroscopy

Abstract: Nanocarrier-based drug delivery is a promising therapeutic approach that offers unique possibilities for the treatment of various diseases. However, inside the blood stream, nanocarriers’ properties may change significantly due to interactions with proteins, aggregation, decomposition or premature loss of cargo. Thus, a method for precise, in situ characterization of drug nanocarriers in blood is needed. Here we show how the fluorescence correlation spectroscopy that is a well-established method for measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 52 publications
3
63
0
Order By: Relevance
“…This low amount of enriched proteins validates the absence of—what is usually termed as—a hard protein corona on these NPs. For pSar‐NPs this is also in line with the FCS study in full blood by Negwer et al [ 42 ]…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This low amount of enriched proteins validates the absence of—what is usually termed as—a hard protein corona on these NPs. For pSar‐NPs this is also in line with the FCS study in full blood by Negwer et al [ 42 ]…”
Section: Resultssupporting
confidence: 88%
“…[ 40,41 ] In addition, it was recently demonstrated that the pSar based nanoparticles maintain their diffusion coefficient and thus hydrodynamic radius even in full human blood. [ 42 ] From the chemical side PEG and pSar follow the Whitesides Rules for protein resistant materials, as they are hydrophilic and only weak H‐bond acceptors without a net charge and H‐bond donor properties. [ 43 ] Moreover, pSar and PEG possess identical solution properties in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, excitation with high‐intensity light can provide a highly localized “burst” of the cytotoxic species precisely at the desired sites. Moreover, the use of fluorescently labeled nanocarrier can be useful to gain insights into the delivery process . Two‐photon fluorescence microscopy represents a valuable tool in this regard.…”
Section: Methodsmentioning
confidence: 99%
“…Klein et al recently reported on the ability of polysarcosine to shield siRNA lipoplexes and analyzed the in vivo stability and biodistribution while Koynov and coworkers demonstrated that pSar shielded nanoparticle maintain their size even in human blood. [39,40] Moreover, the unimolecular character of star polymers seems highly beneficial for extracellular stability and results in stable carrier systems without elaborated cross-linking methods. On the one hand, this may prevent the premature release of the cargo in circulation.…”
Section: Introductionmentioning
confidence: 99%